Attorney Competence and Public Confidence: Evolving Standards for Law Schools and Licenses - Shannon Heery; Emily Hughes (Washington University Journal of Law and Policy, 2025)
Public confidence in the rule of law is key to safeguarding the fair administration of justice. This Article examines a common thread linking three rules that the American Bar Association (ABA) adopted to promote public confidence in the legal profession and to ensure attorneys are competent to protect the public’s trust. From law school education to the continuing education of licensed lawyers, each rule focuses on the importance of legal education in the areas of diversity and inclusion in order to ensure attorney competence and public confidence in the rule of law. Starting with the 2016 adoption of Rule 8.4(g) in the ABA Model Rules for Professional Conduct, to the 2017 revision of the ABA’s Model Rule for Minimum Continuing Legal Education, to the 2022 creation of Standard 303(c) in the ABA Standards and Rules governing the Program of Legal Education—the unifying purpose across the three changes is the belief that all lawyers should be required to take continuing legal education in diversity and inclusion because it is crucial to maintaining public confidence in the legal profession, the rule of law, and the fair administration of justice.
Keywords: LegalEducation; DiversityInLaw; PublicConfidenceInJustice